Kepemimpinan Kepala Sekolah sebagai Motivator: Upaya Meningkatkan Kinerja Guru - Abdul Majid, M. Ayi (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2024)
This research was conducted at S.M.A.N. 1 Gondang using qualitative research methods and a case study approach. Research subjects included school principals, deputy principals for curriculum, and teachers. Data was collected through observation, interviews, and documentation, and data analysis was performed using the triangulation method. This research aims to identify the role of the principal as a motivator and strategies used to improve teacher performance at S.M.A.N. 1 Gondang. Apart from that, this research also aims to understand how this role can influence the quality of teaching and the effectiveness of learning in schools. The research results show that the principal acts as a motivator by making himself part of the school's " big family " as a nurturing figure like anyone else. old, as well as taking approaches both directly and indirectly. The strategies implemented to improve teacher performance include: 1) developing discipline, which is the main key to achieving success; 2) participation in training, as a continuous effort to improve the quality of individual teachers; 3) providing motivation, which functions as a stimulus to work enthusiastically; 4) giving awards, as a form of appreciation for teachers with good performance; and 5) creating programs that support improving the quality of teacher performance.